Anuria : Causes And Mangement in Casablanca - Gallouo, Messian; Tsikambu, Austen Clehaude Dibingue; Alafifi, Mahmoud; Alafifi, Rania; Boucbhareb, El Mehdi; Benghanem, M.; Moataz, Amine; Dakir, Mohamed; Debbagh, Adil; Aboutaieb, Rachid (Jour Med Resh and Health Sci, 2022)
Introduction: Obstructive anuria represents a medico-surgical emergency that requires early diagnosis and its management is well codified and standardized based on emergency collaboration between urologist and nephrologist depending on the severity of the clinical picture.In this study, the most common causes are neoplastic or lithiasic obstructions, and retroperitoneal fibrosis Patients and methods: We carried out a descriptive cross-sectional study with retrospective data collection from April to July 2018 and prospective from August 2018 to March 2019. This involved the study of the files of patients hospitalized in the urology department of the Chu ibn Rochd of Morocco.Our study included all adult patients with bilateral or single upper excretory tract obstruction in a single anatomical or functional kidney associated with one of the three KDIGE criteria. Results: We consulted 4143 hospitalization records, 123 (0.029%) had acute obstructive renal failure, only 93 including 58 women and 35 men met our inclusion criteriaThe average age was 59.2 years old .The average consultation time was 7.9 days. The circumstances of discovery were oligo-anuria (41.9%), low back pain (25.8%) anuria, and renal colic (20.4%) hematuria (8.6%). It was discovered incidentally in 3.3% of cases.The diversion was mainly performed by percutaneous nephrostomy in 74.2% of patients and by JJ probe in 25%. Conclusion: Pelvic cancers represent the most common etiology, hence the importance of a complete clinical examination with pelvic examinations and CT without injection. Prevention is based on the early diagnosis of these cancers. The prevalence of obstructive anuria was significant at 0.029% and its overall lethality at 5.3%.